Experimental investigation on sloshing motion in a liquid pool with binarily mixed-density solid particles. (1st September 2022) - Li, Shuo; Cheng, Songbai; Jin, Wenhui; Zeng, Xiangchu; Qin, Yitong
Highlights: New experiments with binarily mixed-density (same size) solid particles conducted. For mass-based densities, weighted harmonic mean provides best predictions. For volume-based densities, weighted arithmetic or Phan's mean gets better results. Rationale of selected effective densities is confirmed by parametric examination. Compared with mixed-size mixture, segregation of different components is mitigated. Abstract: To clarify the effect of unmelted/refrozen core materials on pool sloshing behavior, in our earlier publications several series of experiments were conducted under a variety of mono-density particle-bed conditions. It is found that three typical flow regimes could be recognized, and predictive models are even successfully developed (or extended) to estimate the regime transition over the varied scenarios. In this work, to further understand this behavior within more realistic particle-bed condition, a number of experiments are newly conducted with binarily mixed-density particles. It is verified that for mass-based effective densities, by employing weighted harmonic mean our previously developed model provides the best predictions among the various effective densities. As for volume-based effective densities, performed analyses suggest that by coupling our model with weighted arithmetic mean or the equivalent density proposed by Phan et al., J. Nucl. Sci. Technol., 56 (1) (2019), relatively better predictive results can be achieved. Reasonability of the identified effective densities is further guaranteed by followed examination of experimental parameters.